2015
DOI: 10.1007/s10508-015-0541-1
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Self-Reported Same-Sex and Both-Sex Attraction from Adolescence to Young Adulthood

Abstract: This study examined how sexual attraction varied across age, gender of participant, and gender of romantic partner, from adolescence to early adulthood. Comparisons between same-sex and both-sex attracted individuals were of particular interest. Using the National Longitudinal Study of Adolescent Health (AddHealth), we examined the responses of participants who reported experiencing same-sex attractions or both-sex attractions at least once within four waves (n = 1889). Results indicated that same-sex attracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
4
15
0
1
Order By: Relevance
“…Secondly, attraction fluidity was substantially lower among exclusively heterosexually attracted participants, compared to their non-exclusively heterosexual peers. Although both findings are in line with the existing research on sexual fluidity (Everett, 2015;Hu et al, 2016;Ott et al, 2011;Rosario et al, 2006;Savin-William et al, 2012;Savin-Williams & Ream, 2007;Scheitle & Wolf, 2018), the observed difference in attraction fluidity might be developmentally specific to adolescents around the age of 16 and up to two years later. The direction in which adolescents are moving with regard to their sexual orientation identity or attraction may be sensitive to age and should thus not be generalized to other age groups.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Secondly, attraction fluidity was substantially lower among exclusively heterosexually attracted participants, compared to their non-exclusively heterosexual peers. Although both findings are in line with the existing research on sexual fluidity (Everett, 2015;Hu et al, 2016;Ott et al, 2011;Rosario et al, 2006;Savin-William et al, 2012;Savin-Williams & Ream, 2007;Scheitle & Wolf, 2018), the observed difference in attraction fluidity might be developmentally specific to adolescents around the age of 16 and up to two years later. The direction in which adolescents are moving with regard to their sexual orientation identity or attraction may be sensitive to age and should thus not be generalized to other age groups.…”
Section: Discussionsupporting
confidence: 90%
“…Although the prevalence of sexual fluidity in adults (i.e., ages 18+) is relatively well documented (e.g., studies assessing outcomes longitudinally, such as the General Social Survey; Scheitle & Wolf, 2018), longitudinal surveys in adolescence (i.e., ages 13-18) are rare. The AddHealth survey (Hu, Xu, & Tornello, 2016;Li, Pollitt, & Russell, 2016;Savin-Williams, Joyner, & Rieger, 2012;Savin-Williams & Ream, 2007), and the Growing Up Today Study (GUTS; Katz-Wise et al, 2017;Ott et al, 2011) found that fluidity of sexual orientation identity was higher among young women than men (Ott et al, 2011;Savin-Williams et al, 2012). A third study from New Zealand drawn from a birth cohort (aged 21 to 26 years) found that around 10% of young adults reported change in sexual attraction over two time points (Dickson, Paul, & Herbison, 2003).…”
Section: Sexual Fluidity In Adolescencementioning
confidence: 99%
See 2 more Smart Citations
“…Past work exploring stability and congruence among dimensions of sexual orientation in adolescent populations has found incongruence and instability to be common among sexual minority adolescents (Fasula et al, 2016; Igartua, Thombs, Burgos, & Montoro, 2009; Ott et al, 2011; Priebe & Svedin, 2013; Savin-Williams & Ream, 2007). Studies have demonstrated, however, that the presence of incongruence among the dimensions of sexual orientation persisting into adulthood may cause psychological tensions (Hu, Xu, & Tornello, 2016). Future longitudinal research studies focused on Black bisexual male adolescents should explore potential mental health impacts associated with dimensional incongruence.…”
Section: Discussionmentioning
confidence: 99%